2010
DOI: 10.1080/15700760903342384
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Collective Bargaining and Urbanicity on the Late Hiring of Teachers

Abstract: It is commonly assumed that urban school districts hire teachers late due to issues related to district size and/or restrictions in collectively bargained teacher contracts affecting teacher hiring and transfers between schools. Our investigation of late teacher hiring and collective bargaining is based on a survey of 40 school districts that captured information about teacher transfer and hiring timelines. Findings indicate no differences between collective bargaining districts and non-bargaining districts in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Finally, school board members and district leaders should consider the timing of budget decisions related to personnel. Researchers have demonstrated that approving budgets late in the summer is a primary contributor to rushed hiring decisions (Gewertz, 2003; Liu et al, 2008; Loubert & Nelson, 2010; Reichardt et al, 2006), possibly resulting in decreased P-J fit, P-O fit, and satisfaction. Research in education and other fields has demonstrated that hiring employees who have high levels of P-O and P-J fit can have positive effects on outcome variables such as satisfaction (Davis, 2006; Johnson et al, 2004; Rehfuss et al, 2012; Wheeler et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, school board members and district leaders should consider the timing of budget decisions related to personnel. Researchers have demonstrated that approving budgets late in the summer is a primary contributor to rushed hiring decisions (Gewertz, 2003; Liu et al, 2008; Loubert & Nelson, 2010; Reichardt et al, 2006), possibly resulting in decreased P-J fit, P-O fit, and satisfaction. Research in education and other fields has demonstrated that hiring employees who have high levels of P-O and P-J fit can have positive effects on outcome variables such as satisfaction (Davis, 2006; Johnson et al, 2004; Rehfuss et al, 2012; Wheeler et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, districts with high populations of students who were economically disadvantaged tended to hire the majority of their teachers late in the hiring season (Engel, 2012; Gewertz, 2003; Liu et al, 2008; Reichardt et al, 2006), with as many as 20% of teachers being hired after the beginning of the school year (Engel, 2012). Some researchers have noted that funding issues might be the primary reason districts have to wait to hire teachers (Gewertz, 2003; Liu et al, 2008; Loubert & Nelson, 2010; Reichardt et al, 2006). The uncertainty of personnel budgets can push back the beginning of the hiring process and reduce the pool of available applicants (Reichardt et al, 2006).…”
Section: Review Of the Literaturementioning
confidence: 99%